2011
DOI: 10.2478/v10145-011-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Development of the Hydroecosystem of the Lake Engure and its Influencing Factors

Abstract: Investigations of water chemical composition and biota of Lake Engure have been carried out since 1995 by using standard methods for inland surface waters. Time series of air temperature and precipitation for the Mersrags meteorological station for the period 1928 to 2009 are used for the trend analysis. The results show that the long-term development of the hydroecosystem is related to such environmental factors as the lake's geographical location, basin and morphology, as well as the lake's history and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Gasi ūnait ė et al [68] found that the range of phytoplankton biomass was similar to our study, varying from 10.3 to 30.2 mg/L (the Mērsrags N had a higher biomass formed by diatoms in 2020) and reaching the highest values during an intense A. flos-aquae bloom in 2002 [69]. Compared to the lagoon-type lake Engures, which is connected to the Baltic Sea and is located near the Mērsrags lagoon, where long-term studies have been carried out [70], differences in species composition and phytoplankton biomass are very low (0.13-0.39 mg/L). Contrary to the lagoon phytoplankton communities, lake phytoplankton community structure was more homogeneous.…”
Section: Discussionsupporting
confidence: 83%
“…Gasi ūnait ė et al [68] found that the range of phytoplankton biomass was similar to our study, varying from 10.3 to 30.2 mg/L (the Mērsrags N had a higher biomass formed by diatoms in 2020) and reaching the highest values during an intense A. flos-aquae bloom in 2002 [69]. Compared to the lagoon-type lake Engures, which is connected to the Baltic Sea and is located near the Mērsrags lagoon, where long-term studies have been carried out [70], differences in species composition and phytoplankton biomass are very low (0.13-0.39 mg/L). Contrary to the lagoon phytoplankton communities, lake phytoplankton community structure was more homogeneous.…”
Section: Discussionsupporting
confidence: 83%
“…during 60 years of our observations, this influence is not so obvious without special detailed studies. The trend analysis of temperature series for the period 1970-2009 has shown a statistically significant increase of annual mean temperature (Spriòìe et al, 2011).…”
Section: Climatementioning
confidence: 99%
“…Unfortunately, there are no data on concentrations of biogenic elements before 1995. Since 1995, no major changes have been observed in concentrations of biogenic elements (Spriòìe et al, 2011). For water birds, the most important habitats are (1) coastal, island and slough areas covered with meadow vegetation, and (2) emergent vegetation.…”
Section: Vegetation Successionmentioning
confidence: 99%
“…Connection with the sea through the canal does not substantially affect the fish species communities, mostly being casual as for example migration of salmon Salmo salar, whitefish Coregonus lavaretus and flounder Platichthys flesus in the northern part of the Lake. However, smaller aquatic organisms of benthos have formed specific oligo-and mesohaline species communities in the location where the Lake and sea waters mixing occurs, thereby increasing species diversity of Lake's benthos community (Springe et al, 2011;Kokorîte u.c., 2013). In 1966, the goldfish Carassius auratus auratus was introduced to the Lake.…”
Section: Lake Engurementioning
confidence: 99%
“…For the Lake Engure Nature Park, the core area of the Engure LT(S)ER region, maps of distribution of vegetation, plant and bird species were prepared. The data on soil, sediment and water chemistry (Briede et al, 2000;Kïaviòð et al, 2011a;2011b;Kïaviòð u.c., 2013), analysis of the main influencing factors of Lake Engure (Springe et al, 2011), plant community structure and species distribution (Auniòð et al, 2000;Gavrilova and Baroniòa, 2000;Laime, 2000;Gavrilova et al, 2011;Laiviòð u.c., 2013;Rûsiòa u.c., 2013), available long-term data on population structure of birds (Vîksne, 1997;Vîksne et al, 2011), freshwater and marine aquatic communities (Strâíe, 2000;Kokorîte u.c., 2013;Strâíe u.c., 2013) and sea pollution (Seisuma and Kuïikova, 2000;Seisuma et al, 2011); lake and coastal marine fish (Aleksejevs un Birzaks, 2013;Strâíe u.c., 2013), insect communities (Karpa, 2000;Melecis et al, 2000; were collected and analysed in relation to human activity, including fishery, agriculture, and tourism (Rozîte and Vinklere, 2011;Pençze et al, 2013;Strautnieks and Grîne, 2013). Synthesis of these data allowed to come up with a conceptual integrated model of socio-economic biodiversity pressures and drivers for the Engure LT(S)ER platform.…”
mentioning
confidence: 99%